THE ROLE OF SERVICE QUALITY ON CONSUMER SATISFACTION - Wydyanto, Wydyanto; Hamdan, Hamdan (Dinasti Publisher, 2020)
The role of service quality in shaping customer satisfaction and loyalty is a research model built to determine the contribution of each factor in explaining other factors. To get a good research model using SEM-Covariance data analysis with the Linear Structural Relationship (LISREL) program. Sample data collection using purposive techniques and quota sampling conducted at Pengandaran, Karakatau, Dieng and Pahawang tourist destinations with 162 tourists. The findings of the research model that were built, that to realize sustainability and maintain the existence of travel agents in the future is to carry out aspects of service quality with excellence. Because it is known that service quality is an important factor for travel agents in shaping positive attitudes and behaviors of consumers that match expectations of being committed and being the first choice.